Perancangan Perancangan Evaluasi Proses Pembelajaran Untuk Kurikulum Merdeka - Fitri Rahmadani, Ade; Yudhi Diputra (The Indonesian Journal of Computer Science, 2024)
This study aims to produce a learning evaluation system on the independent curriculum for State Junior High School 5 Pelepat. This system can help schools in the process of capturing and processing value data that still uses tools and uses manual processing methods. In the development of this learning evaluation system, the SDLC (System Development Lifecycle) method is used with a prototype model. Field study methods and literature studies are used for data collection. This information system is created using Microsoft Excel. System testing is carried out by testing aspects of functionality and usability using the black box testing test method. The results of the information system test developed obtained a functionality value of 1 (Very Good), and usability aspect testing obtained results with a percentage of 85% (Very Decent). So it can be concluded that the system built has succeeded in helping schools overcome manual problems in processing independent and feasible curriculum values and ready to use based on the results of the tests carried out.